PENGGUNAAN CITRA LANDSAT MULTI-TEMPORAL UNTUK KAJIAN PERUBAHAN GARIS PANTAI DI JAWA - , Imam Bachrodin; , Prof. Dr. Hartono, DEA, DESS ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Coastal represent dynamic area as their confluence between land and sea ecosystem. Coastline changes have significant importance to study as boundary consideration for sea territory management in certain area. A coastline change is a result from beach material and active both fluvial and marine process. Observations of coastline changes would be more effective using multi temporal Landsat imagery. The study aims to 1) assess the ability of Landsat imagery in monitoring coastline changes, 2) assess the ability of Landsat imagery to determine the coastal landforms and materials, and 3) estimates of coastline change on the beach material. The Landsat image processing method with visual interpretations of mono and multi-temporal for each band to get the appearance of contrast in the manufacture of 1:150.000 scale map of the coastline. Manufacture of the composite band 457 capable to obtain the appearance of landform unit at semi detail scale in the composite image process in order to show landform unit. Seashore material is obtained by visual interpretation of digital processing map product which involves changing landform interpretation into material. Research has show that Landsat MSS, TM and ETM+ image with single band on channel 4 in the TM and ETM+, channel 7 on the MSS which enables to determine sea and land has ability to show Coastline changing up to 1:150.000 scale. The precision of the results obtained interpretation of landforms 90,67% and accuracy 85% for the interpretation of beach material. Estimation of shoreline changes that occur in coastal mud material in the study area have abrasion of 13,66 meters / year, coral beach material 2,52 meters / year, beach materials stones 0,1 meters / year, while the material having the accretion of sand beaches 0,42 meters / year, so that from this research note that the material of mud beach coastline changes at most